The influence of infant sleep problems and sleep training on maternal subjective well-being - Jacomien Muller; Tharina Guse (AOSIS, 2024)
Background: Disturbed sleep during infancy and early childhood can have a detrimental effect on parental sleep and consequently parental well-being. However, there is a paucity of research on how perceived child sleep problems and behavioural sleep interventions as treatment influence maternal subjective well-being. Aim: This study aimed to explore the incidence of subjective well-being in mothers of children with sleep problems and whether implementing two behavioural sleep interventions changed their well-being. Setting: The research was conducted in a community setting, with parents voluntarily approaching a sleep consultancy based in South Africa. Method: Using data from 119 mothers voluntarily approaching a sleep consultancy in South Africa, a pre-test-post-test design was employed to investigate changes in life satisfaction, affect, couple satisfaction, perceived stress and depression approximately 3 weeks after implementation of a sleep intervention. Results: Results indicate that mothers of children with sleep problems experienced moderate to high life satisfaction and positive affect although the presence of moderate negative affect, couple satisfaction and stress and mild depression suggest possible decreased subjective well-being. Conclusion: Findings suggest implementation of graduated extinction and extinction with parental presence sleep interventions may improve life satisfaction, affect, stress and depression but not couple satisfaction in the short-term. Contribution: This study contributes towards understanding the effect of sleep loss on the subjective well-being of mothers and provides preliminary evidence regarding the benefits of two sleep interventions for improving maternal subjective well-being.